The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1053/joca.2002.0829
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of interleukin 17 to human cartilage degradation and synovial inflammation in osteoarthritis

Abstract: These data suggest that IL-17 could contribute to cartilage breakdown and synovial infiltration in OA by inducing both the release of chemokines by chondrocytes and synovial fibroblasts and, in a less extent, the synthesis of IL-1beta by chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 36 publications
1
86
0
2
Order By: Relevance
“…16,17 In addition, IL-17 has been shown to induce the release of chemokines (such as IL-1b and tumour necrosis factor [TNF]-a) by chondrocytes and synovial fibroblasts, contributing to cartilage breakdown and synovial infiltration in osteoarthritis. 13 Others demonstrated that IL-17 inhibited proteoglycan synthesis in rat cartilage, and increased nitrogen monoxide production. 18 Although the aetiology and pathogenesis of osteoarthritis are poorly understood, it is possible that IL-17 may be among the critical mediators of the disturbed processes implicated in osteoarthritis pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In addition, IL-17 has been shown to induce the release of chemokines (such as IL-1b and tumour necrosis factor [TNF]-a) by chondrocytes and synovial fibroblasts, contributing to cartilage breakdown and synovial infiltration in osteoarthritis. 13 Others demonstrated that IL-17 inhibited proteoglycan synthesis in rat cartilage, and increased nitrogen monoxide production. 18 Although the aetiology and pathogenesis of osteoarthritis are poorly understood, it is possible that IL-17 may be among the critical mediators of the disturbed processes implicated in osteoarthritis pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…12 Osteoarthritis shares several characteristics with rheumatoid arthritis, including joint destruction and synovitis. 13 In addition, IL-17 has been shown to be present in synovial fluid from patients with osteoarthritis, 14 but the relationship between serum and synovial fluid IL-17 concentrations and severity of primary knee osteoarthritis remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…78 il17 also contributes to cartilage inflammation by stimu lating chondrocytes and synovial fibroblasts to release chemokines such as il8 and growthregulated α protein (also known as Groα) that are involved in attracting mononuclear cells and in chondrocyte differentiation. 79 However, although the il17 receptor has been clearly identified in chondrocytes, this cytokine does not seem to be produced locally in most cases of oa. 80 il15, a cytokine produced in innate immune res ponses, could be involved in early oa since higher concentrations of il15 are found in the synovial fluid of patients with early oa than in those with endstage oa.…”
Section: Histopathological Features Of Oa Synovitismentioning
confidence: 99%
“…IL-17F was reported to employ IL-17R for signaling and IL-17F and IL-17A could induce IL-17R ubiquitination and DN-TRAF6, a dominant-negative mutant, could block IL-17F but not IL-17A triggered ubiquitination of IL-17R [46]. The IL-17R is ubiquitously expressed in virtually all cells and tissue and its expression was shown on synoviocytes, chondrocytes and synovial endothelial cells [47][48][49]. Expression of different IL-17 homologs (IL-17A, C, E and F) was detected in synovial fluid mononuclear cells from RA patients and different IL-17R (IL-17RA, IL-17RB, C and D) expression was noted in fibroblast-like synoviocytes of RA patients [50].…”
Section: What Is the Most Physiologically Relevant Target Of Il-17a Imentioning
confidence: 99%